Plasmodium falciparum malarial parasites from Brazil lack artemisinin resistance-associated mutations in the kelch13 gene - Chapadense, Francesca (Sociedade Brasileira de Medicina Tropical, 2019)
INTRODUCTION: Mutations in the propeller domain of the Plasmodium falciparum kelch13 (k13) gene are associated with artemisinin resistance. METHODS: We developed a PCR protocol to sequence the pfk13 gene and determined its sequence in a batch of 50 samples collected from 2003 to 2016 in Brazil. RESULTS: We identified 1 K189T substitution located outside the propeller domain of the PfK13 protein in 36% of samples. CONCLUSIONS: Although the sample size is relatively small, these results suggest that P. falciparum artemisinin-resistant mutants do not exist in Brazil, thereby supporting the continuation of current treatment programs based on artemisinin-based combination therapy.